LEGAL AND REGULATORY FUNDAMENTALS OF THE ELECTRIC POWER INDUSTRY IN UZBEKISTAN (Scientific journal of the Fergana State University, 2023)
After gaining independence, Uzbekistan has the opportunity to pursue an independent socio-economic policy in the interests of the republic and its people. It has become an equal subject of international law. This has allowed it to take its rightful place in the world division of labor. The article provides information on the laws, decrees and decrees adopted after the independence of Uzbekistan on the development of the power industry. The legal and regulatory framework of the power industry has been revealed.